2007
DOI: 10.1108/00035590710822134
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the corrosion behavior of aluminum surfaces in presence of fungi using atomic force microscopy and other tests

Abstract: PurposeThis paper seeks to report a preliminary study that was conducted in order to investigate the corrosion behavior of aluminum surfaces in aqueous solution in the presence of microorganisms. For this purpose, the fungus Aspergillus niger was tested in chloride‐containing aqueous media.Design/methodology/approachWeight loss and pH measurements were performed to verify the activity of the fungus on the aluminum surface and the atomic force microscopy technique was used to examine the surface after removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Fungi are known to affect metallic surfaces with a study of Aspergillus niger on aluminum surfaces showing pitting and formation of “hills and valleys” on the coupon surfaces following a 21-day exposure period. It was also observed that the fungus adhered to the surface and this led to the proliferation of the fungal hyphae . The fungus Aspergillus niger has shown accelerated corrosion behavior on magnesium alloys (AZ31B).…”
Section: Microorganisms and Chemical Microenvironment Of Mic Active S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fungi are known to affect metallic surfaces with a study of Aspergillus niger on aluminum surfaces showing pitting and formation of “hills and valleys” on the coupon surfaces following a 21-day exposure period. It was also observed that the fungus adhered to the surface and this led to the proliferation of the fungal hyphae . The fungus Aspergillus niger has shown accelerated corrosion behavior on magnesium alloys (AZ31B).…”
Section: Microorganisms and Chemical Microenvironment Of Mic Active S...mentioning
confidence: 99%
“…Silva et al studied the effect of Aspergillus niger on aluminum coupons using AFM to expose valleys and hills on the aluminum, including pits with mean dimensions of 80 nm in diameter and in width and 9 nm in depth. The AFM allowed for imaging of discrete particle oxides on the surface and suggested that the biofilm had a larger contact area with the bulk liquid environment than with the substrate . Fang et al quantified the bacterial adhesion forces and found the tip–bacterial surface force was −3.9 to −4.3 nN and the adhesion from the periphery to the cell substratum ranged from −5.1 to −5.9 nN, as compared to the cell–cell interface, which ranged from −6.5 to −6.8 nN.…”
Section: Overview Of Mic Detection and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…During their life-cycle, the P. candidum hydrolyzes ester bonds to produce mono-and diacylglycerols, glycerol, and organic and free fatty acids (12,13) , which are corrosive substances. This fungus was chosen because it has been implicated in corrosion processes as much as the genus Aspergillus (14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%
“…Normalmente, os estudos da biocorrosão se baseiam em testes microbiológicos, sendo poucas as referências a métodos alternativos [3,5,26,28,32]. O estudo de corrosão de materiais metálicos é classificado como uma área cientificamente fora de moda, entretanto, é um assunto complexo e interdisciplinar, principalmente no que concerne à ação associada de microorganismos, tendo relevância não só pela possibilidade de redução de perdas econômicas, mas também pela possibilidade de biorremediação de áreas contaminadas por metais pesados [6].…”
Section: Introductionunclassified